2016
DOI: 10.1371/journal.pone.0162889
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic Correlation of the Mini-Mental State Examination: A Voxel-Based Morphometric Study in Older Adults

Abstract: The clinical utility of the Mini-Mental State Examination (MMSE) and its shorter version (SMMSE) is still debated. There is a need to better understand the neuroanatomical correlates of these cognitive tests. The objective of this cross-sectional study was to determine whether lower MMSE and SMMSE scores correlated with focal brain volume reduction in older adults. Participants from the GAIT study (n = 207; mean, 70.9±5.9 years; 57% female; mean MMSE 26.2±3.9; mean SMMSE 5.1±1.1) were evaluated using the MMSE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 30 publications
2
35
0
Order By: Relevance
“…From the 30 items of the whole MMSE that address multiple cognitive domains, we extracted six items which are specifically related to memory function calculated by the following formula: (immediate recall of three words + delayed recall of three words). This subset score, named as a short form of MMSE (SMMSE), is considered to be efficient in screening dementia among older adults with a memory complaint ( Haubois et al, 2011 ), and have reported being correlated with hippocampal volume ( Dinomais et al, 2016 ). We also calculated subtracted scores (MMSE-SMMSE) to represent cognitive functions not related to memory.…”
Section: Discussionmentioning
confidence: 99%
“…From the 30 items of the whole MMSE that address multiple cognitive domains, we extracted six items which are specifically related to memory function calculated by the following formula: (immediate recall of three words + delayed recall of three words). This subset score, named as a short form of MMSE (SMMSE), is considered to be efficient in screening dementia among older adults with a memory complaint ( Haubois et al, 2011 ), and have reported being correlated with hippocampal volume ( Dinomais et al, 2016 ). We also calculated subtracted scores (MMSE-SMMSE) to represent cognitive functions not related to memory.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 5. Correlation plots of cognitive ability (MMSE, dependent variable) versus regional grey matter volume (rGMV, independent variable) ♦ original data [13]; x Rasch corrected for 'counted fraction' distortion ( [14] and [4]). Standard uncertainties are indicated for MMSE ability scores.…”
Section: C: Response Error and Entropy Categorical Observationsmentioning
confidence: 99%
“…MMSE is a widely used parameter to assess cognitive dysfunction (Dinomais et al, 2016;Spering et al, 2012). In this study, there were significant differences in all cognitive scales (MMSE, CDR, CDR-SOB, and GDS) except the GDepS between the vitamin D-deficient and not-deficient groups.…”
Section: Serum Vitamin D As a Potential Biomarkermentioning
confidence: 61%